Therapeutic approaches for SAPHO syndrome from the perspective of pathogenesis: a review of the literature - Yunuo Wang; Mengjiao Gu; Zixiang Zheng; Haixu Jiang; Luyao Han; Hanjing Huang; Yuanhao Wu; Chen Li; Chen Li (Frontiers in Immunology)
Synovitis, acne, pustulosis, hyperostosis and osteitis (SAPHO) syndrome is a rare autoinflammatory disease characterized by cutaneous manifestations and osteoarticular damage. The pathogenesis of SAPHO syndrome has not yet been elucidated, but studies have shown that the abnormal bone metabolism of patients with SAPHO syndrome is most likely due to localized infections that induce immune disorders in the body. Although no standardized treatment protocols exist, based on existing case studies and data from open studies, we propose that the treatment of SAPHO syndrome can be categorized into three areas according to the symptomatic manifestations of the disease: (1) control of focal infections using antibiotics and tonsillectomy; (2) administration of DMARDs to manage disease progression; and (3) bone remodeling therapy with bisphosphonates to address abnormal bone metabolism. Furthermore, a comprehensive treatment approach tailored to the clinical manifestations of the patient can effectively alleviate symptoms and enhance quality of life.